Synthesis, characterisation, structure-activity and structure-property relationship studies of quinazolinones as antimycobacterial agents - Abbott, Chyanne (Department of Chemistry, 2022)
Mycobacterium tuberculosis (Mtb) is the pathogen responsible for Tuberculosis (TB), one of the most prolific killers among communicable diseases, second only to HIV/AIDS. The World Health Organisation (WHO) estimated 10.4 million people contracted TB in 2015, with 1.4 million fatalities recorded in the same year. One of the most prevalent challenges in TB treatment is the emergence of drug resistant strains of Mtb leading to the development of multi-drug resistant and extremely drug resistant TB. The prevalence of multi-drug resistant TB is accelerated and complicated by coinfection of HIV. New drugs with novel modes of action in newer combination therapies can lessen the strain on existing drugs and their associated challenges, especially the emergence of resistance. Quinazolinones have shown a range of biological activities including anti-cancer, enzyme inhibition, receptor antagonists and agonists, antiplasmodial, antibacterial and anti-tubercular activity. Within the context of work undertaken in this MSc dissertation, 2-aminoquinazolinones with promising antimycobacterial activity were identified from previous work in our research group. However, low aqueous solubility was associated with this series of compounds as a major liability, which needed to be addressed given its likely negative impact on the oral bioavailability of the compounds should they progress further. In an effort to address the problem of limited solubility, 2- aminoquinazolinones and quinazolinones incorporating polar, and hydrogen bonding groups were synthesised and evaluated for antimycobacterial activity and aqueous solubility. It was envisaged that these substituents would improve aqueous solubility while retaining antimycobacterial activity. The analogue ethyl (6-bromo-3-(4-carbamoylphenyl)-4-oxo-3,4-dihydroquinazolin-2-yl)carbamate (7d), exhibited the most potent antimycobacterial activity (0.397 µM) but showed very low aqueous solubility (<5 µM).The majority of the 3-(4-hydroxyphenyl)quinazolin-4(3H)-one analogues, except two, showed high solubility but were inactive at the highest tested concentration (<125 µM) in the antimycobacterial assays. Generally, substitution of a methylsulfoxide phenyl group in place of a bromo group in the 2-aminoquinazolinone scaffold, improves the solubility of the new analogues. Although a marked improvement in aqueous solubility can be seen in these quinazolinone analogues only one analogue (7d) exhibited potent antimycobacterial activity (0.397 µM).